Perbanyakan Gembili (Dioscorea esculenta) dan Ubi Kelapa (Dioscorea alata) Menggunakan Bibit Set Mini - Diantina, Surya; Hutami, Sri (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Ubi kelapa and Gembili are potential sources of fungsional food, because of their high nutrition content. But their production and utilization in Indonesia remains lack behind, due to their low economic value, requiring long cultivation period and high number of tuber-seeds. Experiment was conducted to identify an efficient seed propagation method using miniset cutting. The experiment was carried out at Cikeumeuh ExperimentalStation, Bogor from December 2011 to January 2013. Tuber-seeds of ubi kelapa was divided into miniset cutting of two, six and eight cuttings. For gembili, tubers were cut into two, three and four miniset cuttings. The whole tuber was served as control. Cutting were germinated in polybag, after 30 days the plants were transferred to the field. Each treatment was replicated six times, with one mother tuber as an experimental unit. Plant derived from tuber without cutting produced 463 grams of ubi kelapa seed, while tuber cut into 8 miniset cutting produced 2,986 grams, where the number of tuber seeds were 3 times more than that without cutting. Gembili cut into 4 miniset cutting produced 315 grams of tuber seed with the number of tuber seed 6 times more than that without cutting. Using the miniset cutting could speed up the rate of propagation of both gembili and ubi kelapa seeds.